COMMUNICATIVE LANGUAGE TEACHING’ AND ITS RELEVANCE TO THE LIBYAN ENGLISH LANGUAGE TEACHING CONTEXT - Jahbel, Khalil S.M. (Universitas Muhammadiyah Metro, 2017)
The main purpose of this paper is to investigate the relevance of the communicative language teaching (CLT) to the teaching English in Libyan context. Moreover, it was intended to highlight the historical perspective, features and principles of CLT, followed by an illustration and discussion of the description of the specific classroom context. Finally, after discussing all the elements that are pertaining to this approach, it concluded that CLT seems to be an appropriate approach that may remain on top of a variety –list of approaches, since it focuses on all the language aspects such as functional and grammatical elements and also its tasks imply working with real life situations.